"Let me know when I'm needed": Exploring the gendered nature of digital technology use for health information seeking during the transition to parenting. (October 2021) - Hiebert, Bradley; Hall, Jodi; Donelle, Lorie; Facca, Danica; Jackson, Kim; Stoyanovich, Ewelina
This paper presents results of a qualitative descriptive study conducted to understand parents' experiences with digital technologies during their transition to parenting (i.e. the period from pre-conception through postpartum). Individuals in southwest Ontario who had become a new parent within the previous 24 months were recruited to participate in a focus group or individual interview. Participants were asked to describe the type of technologies they/their partner used during their transition to parenthood, and how such technologies were used to support their own and their family's health. Focus group and interview transcripts were then subjected to thematic analysis using inductive coding. Ten focus groups and three individual interviews were conducted with 26 heterosexual female participants. Participants primarily used digital technologies to: (1) seek health information for a variety of reproductive health issues, and (2) establish social and emotional connections. The nature of such health information work was markedly gendered and was categorized by 2 dominant themes. First, "'Let me know when I'm needed'", characterizes fathers' apparent avoidance of health information seeking and resultant creation of mothers as lay information mediaries. Second, "Information Curation", captures participants' belief that gender biases built-in to popular parenting apps and resources reified the gendered nature of health and health information work during the transition to parenting. Overall, findings indicate that digital technology tailored to new and expecting parents actively reinforced gender norms regarding health information seeking, which creates undue burden on new mothers to become the sole health information seeker and interpreter for their family.